Primary Ewing’s sarcoma of the kidney: A case report - Alasmari, Faris (Int J Surg Case Rep, 2017)
This is a 15-year-old female who presented with sudden onset left flank pain associated with nausea and vomiting and a history of weight loss. Radiological investigation revealed a large non-obstructive tumor involving the lower pole of the left kidney which was primarily thought to be a renal cell carcinoma. She underwent left open radical nephrectomy with adrenalectomy. Histopathology of the resected specimen showed features of Ewing’s sarcoma of the kidney which was confirmed by cytogenetic analysis. This is a rare disease especially in the pediatric group and in reporting such a rare case we hope it helps in identifying a potential course of the disease and its response to the involved treatment.